Accreditation of Degree Programme in Engineering & Technology - Deshpande, M. U. (Journal of Engineering Education Transformations, 1997)
Accreditation has currently become the latest buzz-word among the academia after the launch of the National Assessment of Accreditation Council by the UGC (for universities and colleges offering programme in social and physical sciences) and of the National Board of Accreditation (NBA) by the All India Council for Technical Education (AICTE) for programme in Engineering and Technology.